Uma nova interpretação acerca do impacto da frenagem magnética e interação de maré na evolução da rotação estelar - Santiago, Thiago de Melo (2024)
Stellar rotation is a physical property that controls stellar evolution and influences the evolution of planetary systems in terms of the formation of atmospheres and the establishment of habitable conditions on these planets. The mechanisms of loss and/or transfer of angular momentum by magnetic fields throughout stellar evolution are still under intense debate. Magnetic braking by stellar winds is one of the longest-lasting mechanisms that acts to reduce the angular momentum of stars. With the photometric data and orbital parameters that have been made available mainly by space missions such as Kepler and Transiting Exoplanet Survey Satellite-TESS, it is possible to test models that consider the influence of magnetic braking by stellar winds together with tidal effects resulting from star-planet interaction in a context of equilibrium tides. In the present study, we propose the use of a non-extensive statistical model characterized by a q index to describe the rotation evolution of stars under magnetic braking without the presence of planets and companion stars, as well as considering the superposition of possible tidal effects resulting from star-planet interactions. The deviations of the q values from the Skumanich index were calculated by crossing catalogs containing photometric data obtained by the Kepler mission, resulting in a sample of 16,220 active stars in the red giant and main sequence stages. From a data set comprising 152 planetary systems, totaling 200 exoplanets with masses between 0.4 Earth masses and 20 Jupiter masses, orbital periods between 0.3 and 225 days and semi-major axis measurements less than one astronomical unit , we refined our sample to restrict ourselves to systems with a single star and with stellar masses below the Kraft limit, considering various regimes of orbital rotation period and stellar rotation. In the context of magnetic braking as the only effect present, it was found that the braking index is in the range 1 ≤ q ≤ 3, therefore being consistent with the predictions of the magnetized stellar wind model and presenting transitions between the extreme values for stars more massive than 1.3 solar masses and fast main sequence rotators. From the analysis of the tidal interaction index q, a strong anticorrelation is noted between the tidal index in relation to mass and the planetary radius and, in most of the systems examined, the impact of this interaction is reduced to values with q < 4 and therefore the evolution of stellar rotation is predominantly driven by the magnetized stellar wind, placing the tidal interaction in a secondary role. Furthermore, for planetary systems with index q > 4, the rotational evolution of stars inhabiting planets with semi-major axis measurements smaller than the corotation radius remains largely affected by tidal interaction.